Tussen kolonialisme en postkolonialisme: Thomas Arboussets Excursion missionnaire dans les Montagnes bleues - Zurings, Bert (University of the Free State, 2007)
This article presents a postcolonial analysis of Thomas Arbousset’s Excursion missionnaire dans les Montagnes bleues. In his travelogue, Arbousset describes his experiences with King Moshoeshoe and the Basotho people, culture and country. Because Arbousset was not just a missionary, but also an explorer, natural historian and ethnographer, his relations to the “O/other” are strikingly diversified. In four different sections corresponding to Arbousset’s pursuits, these relations are critically analysed by making use of recent postcolonial insights. Before doing so, however, an introduction and a terminological reflection will be provided. The outcome of the article will be that, although Arbousset is not able to free himself from colonial views entirely, he adopts an unusually respectful attitude towards the Basotho.

In dit artikel wordt een postkoloniale analyse van Thomas Arboussets Excursion missionnaire dans les Montagnes bleues betracht. Arboussets reisbeschrijving geeft zijn ervaringen met koning Moshoeshoe en het Basothovolk, -cultuur en -land weer. Aangezien Arbousset niet enkel een missionaris, maar ook een ontdekkingsreiziger, naturalist en etnograaf was, zijn diens verhoudingen met het/de “andere” sterk gediversifieerd. In vier, met Arboussets bezigheden overeenkomende secties zullen die verhoudingen kritisch geanalyseerd worden op basis van recente inzichten uit de postkoloniale literatuurstudie. Eerst zal echter een inleiding en een terminologische beschouwing gegeven worden. Uit de conclusie van het artikel zal blijken dat, ondanks dat Arbousset zich nooit helemaal kan losmaken van koloniaal gedachtegoed, hij toch een verassend respectvolle houding ten opzichte van de Basotho aanneemt.
Keywords: Arbousset, Thomas; Montagnes bleues; Postcolonial analysis; Basotho people; Missionary